Adoption of requirements engineering and software testing syllabuses in universities: The malaysian landscape - Solemon B. (Institute of Advanced Scientific Research, Inc., 2023)
This paper presents the results of the survey perform to investigate the requirements engineering (RE) and software testing (SWT) courses offering by universities in Malaysia since the rollout of the Malaysia Software Testing Hub Academic Outreach program in 2017. Due to limited resources, the survey focuses to the top thirteen Malaysias universities of the QS World University Rankings 2019. The information of the academic programs and courses were gathered from the official website of these universities. The analysis performed to the publicly available information in the official websites shows several universities do not disclose their program structures and detailed course information. From the available information, it can be concluded that majority universities (9 or 70%) are offering RE and/or SWT courses or their variation courses such as Systems Analysis and Design, which is the body of knowledge of Information System discipline defined in the recent Computing Program Standard by Malaysian Qualifications Agency. Also, the RE and SWT courses or variation of the courses are offered in the Computer Science, Computer Science with Software Engineering specialization, Software Engineering and Information Technology bachelor degrees. Analysis performed to detailed information of RE courses offered by four universities shows almost all learning objectives of the courses are designed to meet the L2 or mastering and using knowledge level of CPRE-FL syllabus. On the other hand, the learning objectives of SWT courses offered by UM and UTP are designed to achieve the K2 or understand and K3 or apply cognitive knowledge levels of CTFL syllabus. 2019 Institute of Advanced Scientific Research, Inc. All rights reserved.